PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN KEMAMPUAN MENGGAMBAR IMAJINATIF SISWA KELAS III SDN 85 PEKANBARU - Gusriani '; Zufriady '; Munjiatun ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrak : Problem in this study is the low of student ability in making imaginative drawing on the lessons of Cultural Arts and Skills. For that we need to be improved in order to enhance the students' ability to create imaginative pictures. Efforts to repair by applying direct instructional model to enhance the ability to draw imaginative. This research is classroom action research. The research was conducted on third grade students at SDN 85 Pekanbaru academic year 2014/2015. Time of the research was conducted on 21 November 2014 until 6 December 2014. The subject of research is the third grade students of SDN 85 Pekanbaru which contains of 37 students; they are consisting of 17 men and 20 women. Data collection techniques used observation techniques and tests. Data analyzing technique used the activities of teachers and students, the form of product assessment process and results. The results showed that the average scores of students was 59.57, has increased in the first cycle of UH I to 64. Has an increased of 4.43. In second cycle of UH II became 72.67, has increased 8.67 from a first cycle. In the first cycle of teacher activity for first meeting with an average of 65 and second meeting have improving to 75. The second cycle for first meeting with an average of 85 and second meetings is 95. Then the student’s activity in the first cycle for the first meeting with an average of 65% and has increased in the second meeting to 75%. Then the first meeting of the second cycle increased to 90% and in the second meeting increased to 95%. From the above explanation shows that the application of direct learning model can improve the ability to draw imaginative third grade students of SDN 85 Pekanbaru.Keywords: Direct Learning, Improving Imaginative Drawing Ability